Engineering ultra-permeable and antifouling water channel-based biomimetic membranes toward sustainable water purification - Li, Xuesong (2023)
Water channel-based biomimetic membranes (WBMs) are gaining increasing attention due to the effectiveness of water channels in enhancing water permeability and breaking the permselectivity trade-off. However, the ultra-permeable WBMs may suffer from severe membrane fouling issue because a high-water flux tends to result in an accelerated fouling and thus compromises the benefits gained from the usage of water channels. Herein, a novel in-situ modification protocol was proposed to enhance the antifouling performance of ultra-permeable WBMs. The nanovesicles incorporated with aquaporin (AQP) water channels were functionalized with polyethylene glycol brushes (i.e., PEGylation) via a facile self-assembly approach and subsequently encapsulated in the selective layer of thin-film composite membranes through interfacial polymerization. The modification had minimal impact on the function of AQPs, resulting in WBMs with a high water permeance (∼8.2 LMH/bar) and good NaCl rejection (96.4%) comparable to the unmodified WBMs. Moreover, the in-situ modification drastically enhanced the surface hydrophilicity, which endowed the membrane with a superior fouling resistance to organic foulants. The improved fouling resistance ensured a more sustainable operation of ultra-permeable WBMs, particularly in scenarios that favor high water fluxes. This facile modification strategy provides an efficient way to fabricate ultra-permeable and antifouling WBMs for sustainable water purification.